Simplify and write the equation with positive exponents
To make a negative exponent positive, move the base and its exponent to the opposite location in the fraction (reciprocation). That is, a-n = 1/an and 1/a-n = an.
Using the laws of exponents, we can prove the above by the following:
an • a-n = an+(-n) = a0 = 1 ; therefore, a-n = 1/an (where a≠0).
With this, (2xy3)-2 = 1/(2xy3)2
1/(2xy3)2 = 1/(22x2(y3)2)
A negative exponent means that you take the reciprocal of what is being raised to the power. For example,
x-1 = 1/x
(1/y)-2 = y2
That being said, (2xy3)-2 = 1/(2xy3)2 or 1/(4x2y6)